Syn‐rift volcanism in the Barmer Basin: An intra‐basin extrusive complex at the northern limit of the Deccan volcanic province in India. Issue 3 (11th December 2022) - Burley, Stuart D.; Gould, Thomas; Taylor, Andrew; Mishra, Premanand
Abstract : The Raageshwari Volcanic Formation (RVF) is a volcanic complex in the southern part of the Barmer Basin, NW India, localized around a large rift centre horst block, the Central Basin High. The RVF comprises an initial sequence of acid igneous rocks, which are of ignimbritic origin, termed the Agni Member, overlain by a stacked sequence of basaltic lava flows interbedded with subordinate pyroclastic deposits, the Prithvi Member. Seismic data confirms that the volcanic complex has a conical overall geometry and a layered internal structure produced by successive and extensive flows of basalt and ignimbrite, very similar to that observed in the main Deccan lava outcrops along the western margin of India. U–Pb zircon ages near the top of the Agni Member in the Raageshwari‐26 well give an age of 68+/−2 Ma for a tephrite pyroclastic unit, whilst Ar–Ar analysis of a distal basalt containing phenocrysts of biotite from the Saraswati‐4 well gave an older robust Ar–Ar plateau age of 73.7 ± 1.4 Ma. A typical Deccan age of 67.9 ± 1.7 Ma was obtained from the isolated unaltered basaltic andesite in well NE‐South‐1. Due to depositional on‐lap onto the Central Basin High, the overlying alluvial Dandlawas and Fatehgarh formations are absent on the crest of the Central Basin High and Barmer Hill Formation lake sediments rest directly on the basalts. This relationship indicates that the volcanic cone was a structural or topographic high during deposition onto which the Fatehgarh and Barmer Hill formations lake sediments eventually on‐lapped. The RVF of the Barmer Basin along with the Deccan volcanics in the Cambay Basin, Narmada Rift and in Saurasthra are all developed within fault‐bounded rift basins, in which deep seated faults extend beneath the Deccan volcanic sequence. They are associated with thermal anomalies and thinned continental crust and the presence of a linear low velocity zone at 100 km depth in the upper mantle region beneath the Barmer and Cambay basins. This is interpreted to be the position of the "conduit" through which plume head material passed through the upper mantle before arriving at the base of the Indian lithosphere. The RVF therefore appears to be an early eruption of differentiated ultrabasic magma from a shallow, secondary magma chamber produced by partial crustal melting. Abstract : The Raageshwari Volcanic Formation (RVF) is a volcanic complex in the Barmer Basin, localized around a rift centre block, comprising a sequence of basaltic flows interbedded with pyroclastic deposits. It is associated with thinned continental crust, interpreted to be the position of the "conduit" through which plume head material passed.